RELASI PERUBAHAN NILAI TUKAR RUPIAH DENGAN DOLAR AMERIKA TERHADAP KINERJA KEUANGAN PERUSAHAAN PERHOTELAN DAN BIRO PERJALANAN YANG GO PUBLIC DI BEJ JAKARTA - K. Rahyuda; Adi Krisna (Universitas Trisakti, 2003)
The revenue for hotel and travel services industries, mainly, are generated from room sale that generally price are quoted in dollar American. Since mid 1997, Indonesian's economic face a crisis that was stimulated by depreciation of rupiah against foreign currency, foremost with US dollar. It was an advantage for hotel industries, as the amount in rupiah received increasingly, and tourist more interest with local product.The influence of exchange rate to financials performance of hotel industries need a deeply research to find (1) relation between exchange rate with financials performance of hotel industries, (2) which financial ratios are significantly related with exchange rate.Objects of this research are hotel and travel services industries those have been listed in Jakarta Stock Exchange since 1997 until 2000. Out of eleven listed companies, were taken 7 companies as sample. By utilizing Pearson correlation method, to find out the coefficient of correlation, direction and level of significant.Research was conducted individually in each companies and industrial average. The re-search indicated both individually and industrial average, exchange rate was significantly related with capital structure's ratios and profitability ratios. Capital structure which consist of American's dollar, due to appreciation of American dollar against rupiah, interest cost was increase more than revenue increase, therefore its reducing net income.